Pengaruh Jaminan Obligasi, Umur Obligasi, Interest Coverage Ratio, dan Manajemen Laba terhadap Peringkat Obligasi - Suwarmelina Suwarmelina (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to examine the effect of bond guarantees, bond age, interest coverage ratio, and earnings management on bond ratings of bond issuing companies listed on the Indonesia Stock Exchange in 2016-2019. Determination of the sample using purposive sampling method. The number of samples selected was 37 companies. The data analysis technique used is multiple linear regression using the Eviews 11 Student Lite program. The results of this study indicate that bond guarantees affect bond ratings, bond age has no effect on bond ratings, interest coverage ratio affects bond ratings, and earnings management affects bond ratings.